Emotional expectations and emotional control of colorectal cancer patients after colostomy - Glińska, Jolanta; Malesza, Monika; Lewandowska, Małgorzata; Miller, Renata; Dziki, Łukasz; Dziki, Adam (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2013)
Introduction: Cancer is a particularly hard time for all people. Nowadays, the negative influence of colostomy on the emotional state of the colorectal cancer patients is more and more noticeable. Potential life-threatening situations stimulate patients’ defense reflex by repressing the emotions that might negatively affect the quality of patients’ life. Aim of the study: Evaluation of the need for psychological support and emotional control of colorectal cancer patients after colostomy depends on demographical factors. Material and methods : The study was performed in 2012-2013 among 50 members of the Ostomy Association of Lodz using the Emotional Control scale and a list of patients’ expectations. The study was performed using Courtauld Emotional Control Scale, CECS, (Watson and Greer) and Patient Request Form (PRF) (Salmon & Quine) – both in Z. Juczyński adaptation. Results : Results of the study indicate that the age, sex, educational level and place of residence have a great influence on the level of repressing negative emotions (p < 0.05). The need for emotional support differs depending on the time of the patients’ treatment. The most numerous group of the patients (f 1 = 0.7) received emotional support from family. The second most numerous group received emotional support from medical staff (f 1 = 0.5). A worryingly low number of patients (f 1 = 0.08) received emotional support from the psychologist. Conclusions : Patients require more emotional support after the surgery than before it. Moreover, the need for emotional support and the level of repressing negative emotions increase with the age of the patients. Patients who live in the city have a greater ability to control negative emotions, whereas the higher educational status the lower level of repressing negative emotions.